Long-term employability and talent: upcoming educational challenges and emergencies - Alessandrini, Giuditta (Formazione & insegnamento, 2018)
The paper, starting from a reflection on the role of the capability approach on the pedagogical debate on training, is structured in three points: 1) a photography of work scenarios with particular regard to increasing polarization; 2) the challenge of agency, that is a reflection about the new skills needs also referring to the scenarios of the fourth industrial revolution; 3) the reflection on talent as a subjective right to the achievement of capabilities.